2014
DOI: 10.1101/gad.246538.114
|View full text |Cite|
|
Sign up to set email alerts
|

Human nonsense-mediated RNA decay initiates widely by endonucleolysis and targets snoRNA host genes

Abstract: Eukaryotic RNAs with premature termination codons (PTCs) are eliminated by nonsense-mediated decay (NMD). While human nonsense RNA degradation can be initiated either by an endonucleolytic cleavage event near the PTC or through decapping, the individual contribution of these activities on endogenous substrates has remained unresolved. Here we used concurrent transcriptome-wide identification of NMD substrates and their 59-39 decay intermediates to establish that SMG6-catalyzed endonucleolysis widely initiates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
205
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(221 citation statements)
references
References 84 publications
12
205
1
Order By: Relevance
“…4C). Consistent with a previous study reporting an overrepresentation of snoRNA host genes among NMD targets (Lykke-Andersen et al 2014), snoRNA host genes are threefold enriched among our top 1000 hits, when compared to FIGURE 3. SMG6 and SMG7 dKD and individual rescues reveal the highly redundant activity of these two NMD factors.…”
Section: Identification Of Nmd-targeted Transcriptssupporting
confidence: 77%
See 1 more Smart Citation
“…4C). Consistent with a previous study reporting an overrepresentation of snoRNA host genes among NMD targets (Lykke-Andersen et al 2014), snoRNA host genes are threefold enriched among our top 1000 hits, when compared to FIGURE 3. SMG6 and SMG7 dKD and individual rescues reveal the highly redundant activity of these two NMD factors.…”
Section: Identification Of Nmd-targeted Transcriptssupporting
confidence: 77%
“…Among the NMD-targeted genes, we found a significant enrichment of miRNA host genes, in addition to the already reported snoRNA host genes (Lykke-Andersen et al 2014). Many noncoding RNAs also appear to be targeted by NMD, depending on the presence of open reading frames (ORFs) in their sequence, consistent with recent reports showing ribosome association of many supposedly noncoding transcripts (Ingolia et al 2014).…”
Section: Introductionsupporting
confidence: 75%
“…The emetine and cycloheximide data presented here lead us to hypothesize that, at least for a subset of cytoplasmic lncRNA transcripts, ribosomal recruitment results in degradation. The exact mechanism for this was not tested here, although an obvious candidate would be the translation-coupled nonsense-mediated decay (Lykke-Andersen et al 2014). If NMD is responsible, then one testable hypothesis would be that single-exon transcripts (lacking the exon junction complexes required for NMD) should be unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed by Chew et al (2013) that lncRNAs on the ribosomes are subject to degradation by the nonsense-mediated decay (NMD) pathway. Indeed, reports exist in human of ribosome-dependent degradation of snoRNA host genes (Makarova and Kramerov 2005;Lykke-Andersen et al 2014), and this effect is reported to be widespread in plants (Kurihara et al 2009) and for unannotated RNAs in yeast (Smith et al 2014). Using the same candidate genes as before, we tested whether stalling of ribosomal elongation influenced lncRNA stability (Fig.…”
Section: Stability Levels Of Ribosome-associated Lncrnas Are Sensitivmentioning
confidence: 99%
“…28 The expression of these noncoding RNAs is closely linked to the expression of their host mRNAs, and for snoRNAs, it has been suggested that their host mRNAs are merely a byproduct of the snoRNA production process. 29 Also, many different noncoding RNAs (including snoRNAs, lncRNAs, and sno-lncRNAs) are being recognized as regulators of alternative splicing. The lncRNA MALAT1, for example, has been shown to regulate the expression level, localization, and activity of SR proteins (serine/arginine-rich proteins).…”
Section: Splicing and Noncoding Rnasmentioning
confidence: 99%